Sistem Pendaftaran Penerimaan Bantuan Sembako Bagi Masyarakat Orang Asli Papua Pada Dinas Perdagangan Kabupaten Nabire - Natalia Paisey; Kristia Yuliawan; Gunawan Prayitno (Jurnal Teknologi dan Informatika, 2023)
The system of registration of assistance at the Department of Commerce is still manual. Where employees of the Trade Office office still store data on street vendors are still files and do not have a database where when looking for the information needed, they have to open files that are long and take a long time.